ANALISIS TINGKAT KEPUASAN KERJA KARYAWAN PADA PT. REMALA ABADI TBK - Suci, Ratu Balqis Dipomustika; Lutviani, Metya (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the level of employee job satisfaction towards the company at PT Remala Abadi. Job satisfaction is one of the important factors that affect employee productivity and loyalty in an organization. The method used in this study is a quantitative method with a survey approach by distributing questionnaires to all employees who are respondents. Data were analyzed using a Likert scale and analyzed based on the calculation of actual scores, ideal scores, and percentage levels of satisfaction. The results of the study showed that the level of employee job satisfaction at PT Remala Abadi reached 80%, which is included in the high category. This reflects that most employees are satisfied with various aspects of the work environment, including relationships with superiors, work facilities, updates, and internal communication. However, there are still several aspects that need to be considered to be improved, such as training new employees and providing certain work facilities. With these results, the company is expected to be able to maintain factors that have provided high satisfaction and make continuous improvements to aspects that are still considered less than optimal.